Anatomical Variations of the Greater Palatine Canal and Greater Palatine Foramen in an Iranian Subpopulation Using Cone-Beam Computed Tomography: CBCT Evaluation of Greater Palatine Canal - Ghaznavi , Aisan; Mostafavi , Maryam; Alamdari Mahd, Mandana (Journal of Dental School, 2023)
Objectives This study aimed to assess the anatomical variations of the greater palatine canal (GPC) and greater palatine foramen (GPF) in an Iranian subpopulation using cone-beam computed tomography (CBCT). Methods This cross-sectional study was conducted on 193 CBCT scans of adults (94 males, 99 females) taken between 2017-2021 that were retrieved from a radiology clinic in Urmia, Iran. Axial sections were used to assess the position, diameter, and shape of GPF, and sagittal sections were used to assess the length and path of GPC. Data were analyzed by paired and independent t-test, Wilcoxon test, Mann-Whitney test, and Chi-square test (alpha=0.05). Results In most cases (97.34% of males and 98.49% of females), GPF was located distal to the maxillary first molar. The mean distance between the GPF and midpalatal suture was significantly greater in males than females (15.2±1.8 vs. 14.3±1.5 mm; P=0.002). The mean diameter of GFP was significantly larger in males than females in both mesiodistal (2.34±0.64 vs. 1.96±0.63 mm, P<0.05) and anteroposterior (4.69±1.17 vs. 4.07±1.20 mm, P=0.001) dimensions. The mean length of GPC in males was significantly higher than that in females (28.55±2.62 vs. 26.90±3.31 mm, P<0.05). The most common form of GPF and GPC (on sagittal sections) was oval, and sigmoid, and curve, respectively. The most common GPC path was anterior-inferior (65.96% of males and 64.65% of females). Conclusion The present results provided valuable information regarding the anatomical variations of GPF and GPC in Iranian population. CBCT was proven to be a valuable tool for assessment of maxillofacial anatomical landmarks